2017
DOI: 10.1042/bcj20160992
|View full text |Cite
|
Sign up to set email alerts
|

Identification of TBK1 complexes required for the phosphorylation of IRF3 and the production of interferon β

Abstract: The double-stranded RNA mimetic poly(I:C) and lipopolysaccharide (LPS) activate Toll-like receptors 3 (TLR3) and TLR4, respectively, triggering the activation of TANK (TRAF family member-associated NF-κB activator)-binding kinase 1 (TBK1) complexes, the phosphorylation of interferon regulatory factor 3 (IRF3) and transcription of the interferon β (IFNβ) gene. Here, we demonstrate that the TANK–TBK1 and optineurin (OPTN)–TBK1 complexes control this pathway. The poly(I:C)- or LPS-stimulated phosphorylation of IR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 49 publications
1
52
0
Order By: Relevance
“…5C), suggesting that other unknown signaling molecules or feedback loops may also contribute to the regulation of different chemokines. LPS also has the ability to activate TBK1 to coordinate the activation of the IRF3 and NF-κB pathway in immune cells (39, 40). LDK378 also inhibited the LPS-induced phosphorylation of TBK1, IRF3, and p65 (fig.…”
Section: Resultsmentioning
confidence: 99%
“…5C), suggesting that other unknown signaling molecules or feedback loops may also contribute to the regulation of different chemokines. LPS also has the ability to activate TBK1 to coordinate the activation of the IRF3 and NF-κB pathway in immune cells (39, 40). LDK378 also inhibited the LPS-induced phosphorylation of TBK1, IRF3, and p65 (fig.…”
Section: Resultsmentioning
confidence: 99%
“…3c). This prompted us to examine the levels of Tbk1, the protein that forms a complex with a variety of proteins ultimately resulting in activation of IRF3 31 , and Lgp2, a negative regulator of Rig1 32,33 . In keeping with the muted IRF3 response, we find that Tbk1 is downregulated and Lgp2 is robustly induced (4.2-fold) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that in the RLR signaling pathway, VISA/MAVS activates TBK1/IKKε via TRAFs proteins, and the combined deletion of TRAF completely abolishes the MAVS-TBK1/IKKε interaction and subsequent TBK1/IKKε activation [8,[10][11][12]. It was experimentally confirmed that MAVS recruits and activates TBK1/IKKε upon RNA virus infection through a preassociated TRAFs-TBK1/IKKε complex, resulting in activation of TBK1-IRF3 and type I IFN production [13].…”
Section: Introductionmentioning
confidence: 89%